Dinamika Ekonomi Makro dan Pendapatan Nasional: Analisis Dampak Deflasi Pertama dalam Dua Dekade di Indonesia - Pahlevi, Davin Prayoga; Angraini, Anggita; Ginaristi, Eka Putri; Kamila, Shafa; Dianto, Ari Tri; Nuraya, Ahmad Setiawan (Innovative: Journal Of Social Science Research, 2025)
Deflation is an economic phenomenon characterized by a continuous decline in the general price level of goods and services. This study examines the impact of deflation on consumption, investment, and economic growth in Indonesia using a quantitative approach with descriptive and inferential analysis. Data from 2000 to 2024 obtained from the Central Bureau of Statistics (BPS) and Bank Indonesia were analyzed using linear regression. The results show that deflation has a negative impact on consumption, as households tend to delay spending in anticipation of further price declines. Investment also decreases due to declining business profits and economic uncertainty. Furthermore, economic growth slows down as both consumption and investment contract. Regression analysis indicates a significant positive relationship between the Consumer Price Index (CPI) and GDP growth, implying that deflation negatively affects economic expansion. The study highlights the need for effective monetary and fiscal policies to mitigate the adverse effects of deflation and maintain economic stability. Addressing deflationary risks through proactive government intervention can help sustain long-term economic growth.